Pengaruh Ukuran Perusahaan, Financial Leverage dan Kualitas Audit Terhadap Perataan Laba (Income Smoothing) Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Tahun 2017-2020 - Ni Wayan Sinta Sunetri; Putu Cita Ayu; Putu Nuniek Hutnaleontina (UNHI Press, 2022)
Earnings information is paramount for investors because they can provide an overview of how dividends will be paid when investing their capital. Income smoothing is the practice of profit manipulation to reduce fluctuations in net income over a period of time. This study aims to determine how company size, financial leverage and audit quality affect earnings smoothing in manufacturing companies listed on the Indonesian Stock Exchange over the period 2017-2020. Targeted sampling is used as the sampling method, sample companies based on criteria was 31 companies with an observation period of 4 years, 2017 to 2020, so that 124 research samples were obtained. Eckel index measuring income smoothing using the technique of logistic regression analysis. Theory of eckel is used to calculate income smoothing. Hypothesis testing with logistic regression analysis. Research resultshow that company size, financial leverage and audit quality all have an impact on income smoothing. Firm size has no significant positive effect on income smoothing, financial leverage as measured by debt to equity ratio has no significant negative effect on income smoothing, while audit quality has a significant and negative effect on income smoothing.